Die grosse Abweichungen für die homogenen Markoffschen Kelten - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкявичене. Большие уклонения для однородных цепей Маркова A. Aleškevičienė. Dideli atsilenkimai homogeninėms Markovo grandinėms